Preservasi Digital: Praktik Resiliensi Perpustakaan UNTAR Layanan Bidang Ilmu Psikologi Pada Masa Pandemi Covid-19 - Ayu Yuli Wijayanti (UIN Mataram, 2024)
This study describes the process of digital preservation at the Tarumanagara University Library Services in the Field of Psychology. The aim is to provide an overview of how digital preservation is part of the resilience strategy of the Tarumanagara University Library Services in the Field of Psychology during the Covid-19 Pandemic. Serving collections of scientific works online with digital collection sources is a way that the Tarumanagara University Library Services in the Field of Psychology does during the Covid-19 Pandemic. The availability of digital collections is the key to making online services possible. Interestingly, this digital preservation which has been carried out since 2018 has helped the Tarumanagara University Library Services in the field of Psychology survive and adapt and can still serve users during the Covid-19 Pandemic. This study uses a case study approach with a qualitative descriptive method. Data collection was carried out based on observation and documentation. Data analysis uses the theory of Miles and Huberman's Model which consists of three stages, namely data reduction, data presentation, and drawing conclusions which are used to explain the results of research systematically. The results found in this study are the motive for digital preservation due to obsolescence and damage to collections of scientific works in the form of Compact Disks (CDs). Another reason is to adapt to technological developments. The form of digital preservation that is carried out is in the form of refreshing and is included in the category of long-term preservation.